SST gradient and reconstructed Antarctic Circumpolar Current latitude change in the Southern Indian Ocean over the last 150kyr - Xuyuan E Ai; Lena M Thöle; Alexandra Auderset; Mareike Schmitt; Simone Moretti; Anja S Studer; Elisabeth Michel; Martin Wegmann; Alain Mazaud; Peter K Bijl; Daniel M Sigman; Alfredo Martínez-García; et al. (PANGAEA, 2024)
We report a quantitative and continuous record of the ACC latitude over the last glacial-interglacial cycle derived from biomarker-based reconstructions of surface layer temperature gradient in the Southern Indian Ocean. The surface layer temperature gradient is calculated from two downcore surface layer temperature series reconstructed from TEX86L at sediment cores MD11-3353 and MD11-3357 from the Indian Southern Ocean. The TEX86L-temperature calibration function is revised based on the global core-top data compilation of Tierney and Tingley (2015): SST L (0-200m integrated, °C) = 55.84*TEX86L + 38.15. The past ACC latitude is derived using a quantitative framework that simulates the effect of ACC migration on Southern Ocean surface temperature gradient.